Decision making of participants in cancer genetic counseling - Cruzado, Juan A. (Psicooncología, 2010)
We present an overview of most important variables that influence decision making of participants in cancer genetic counseling. It is studied the following factors: age, gender, personal an family history of cancer, medicalpatient communication, communication and support within family, risk perception, monitoring coping style and self-efficacy, and genetic test outcomes. The decisions of participants in CGO are strongly influenced by beliefs, memories, family comparisons and narratives about cancer, that determine emotions, preferences and values that underlie their decisions, and must be taken into account during the process of genetic counseling. We review the decision aids applied in genetic counseling: Interactive, print, computer or internet. Research results show that decision aids are effective and useful. Also, participants accept and require these aids. Most decision aids are designed for breast / ovarian cancer, while in other types of hereditary cancer are scarce. The decision aids in genetic counselling are developed mainly in USA and Australia. We stress the importance of designing and implementing decisions aids in Spain and Latin America, in order to promote the active role of people at risk of familial cancer and shared decision-making